Are lupus animal models useful for understanding and developing new therapies for human SLE?. Issue 112 (August 2020) - Moore, Erica; Putterman, Chaim
Abstract: Systemic lupus erythematosus is a systemic autoimmune disease driven by a complex combination of genetic, environmental, and other immunoregulatory factors. The development of targeted therapies is complicated by heterogeneous clinical manifestations, varying organ involvement, and toxicity. Despite advances in understanding the mechanisms contributing to SLE, only one biologic drug, belimumab, is FDA-approved. The identification and development of potential therapies have largely been driven by studies in lupus animal models. Therefore, direct comparison of both the therapeutic and immunological findings in human and murine SLE studies is critical and can reveal important insights into indeed how useful and relevant are murine studies in SLE drug development. Studies involving belimumab, mycophenolate mofetil, abatacept, rituximab, and anti-interferon strategies generally demonstrated analogous findings in the attenuation of SLE manifestations and modulation of select immune cell populations in human and murine SLE. While further basic and translational studies are needed to identify SLE patient subsets likely to respond to particular therapeutic modalities and in dissecting complex mechanisms, we believe that despite some inherent weaknesses SLE mouse models will continue to be integral in developing targeted SLE therapies. Highlights: Similar therapeutic and immunological effects are observed in human and murine SLE studies. Studies with belimumab and rituximab treatment reveal resistant B cell populations, present in both human and murine SLE. CyTOF immunophenotyping can identify potential SLE patient clusters more likely to respond to specific therapies. Testing in lupus animal models remains an important avenue in SLE drug development.